Literature Review: Differentiated E-Worksheets to Boost Primary School Learning Outcomes Between 2020-2025 - Zakiyyah, Hana; Sutopo, Yeri; Harianingsih, Tri; Subali, Bambang; Widiari, Nuni (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This article was written to present a literature review on the effectiveness of using differentiation-based E-worksheets in improving the learning outcomes of elementary school students. The method used is Systematic Literature Review (SLR), with a literature review approach to 17 articles and one proceeding indexed by Google Scholar and published between 2020 and 2025. Data were obtained using Harzing's Publish or Perish application. The differentiation-based E-worksheets were developed to adapt learning to students' readiness, interests, and learning styles, and to promote inclusive and adaptive learning. The study results show that consistently using this media can increase student motivation, engagement, and academic achievement. E-worksheets allow teachers to design flexible and contextualized learning materials while supporting various visual, auditory, and kinesthetic learning styles. In addition, this approach also fosters independent, collaborative, and problem-solving-based learning. The findings confirm that differentiation-based E-worksheets are an effective and relevant learning tool in the digital era. The implication is that this media needs to be continuously developed as an innovative solution to the limitations of conventional teaching methods and to better support students' learning needs.